Radiologische Diagnostik entzündlicher Wirbelkörpererkrankungen - Eichler, Markus; Weber, Marc-André; Hähnel, Stefan; Rehnitz, Christoph (Der Orthopäde, 2012)
Back pain is nonspecific and allows a broad range of differential diagnoses. In the early phase of infectious or neoplastic processes conventional diagnostic radiology rarely shows groundbreaking findings. Magnetic resonance imaging (MRI) is the method of choice to detect early changes in the vertebral bodies, intervertebral discs and surrounding tissues. Fluid-sensitive, fat-suppressed sequences (STIR) and contrast media are used to distinguish infections from other diseases. Due to the typical signal intensity in T1 and T2 sequences, infections of degenerative, rheumatic, and neoplastic processes can be defined and allow the initiation of appropriate therapy.
Gesehen am 25.06.2019